2009
DOI: 10.1292/jvms.71.387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lidocaine Hydrochloride on the Function of Bovine Peripheral Leukocytes

Abstract: ABSTRACT. To clarify the effect of lidocaine hydrochloride (Lid) on bovine peripheral granulocyte phagocytosis, adhesion molecule expression of leukocytes and peripheral blood mononuclear cell mRNA expression of cytokines were investigated. Lid was added to blood samples at a final concentration of 0 (only PBS; Cont), 0.2 mg/ml or 2.0 mg/ml. Phagocytosis of granulocytes was significantly decreased by addition of 2.0 mg/ml of Lid. CD18 expression of granulocytes and mononuclear cells were significantly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, at the latter dosage, lidocaine does not exert its beneficial effect as a consequence of impaired neutrophil influx into intestinal mucosa, although other anti‐inflammatory mechanisms may be operative . Because in vitro studies of bovine and canine peripheral blood demonstrate decreased adhesion molecule expression in a dose‐dependent manner and as the threshold for serum lidocaine toxicity is double that of 980 ng/mL, we elected to deliver a higher dosage to potentially maximize our ability to detect a significant lidocaine effect on neutrophilic inflammation. However, in rabbit studies of endotoxin‐induced acute lung injury, delivery of IV lidocaine at 0.03 mg/kg/min (plasma lidocaine concentrations not provided) significantly decreases neutrophilic infiltration into pulmonary parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at the latter dosage, lidocaine does not exert its beneficial effect as a consequence of impaired neutrophil influx into intestinal mucosa, although other anti‐inflammatory mechanisms may be operative . Because in vitro studies of bovine and canine peripheral blood demonstrate decreased adhesion molecule expression in a dose‐dependent manner and as the threshold for serum lidocaine toxicity is double that of 980 ng/mL, we elected to deliver a higher dosage to potentially maximize our ability to detect a significant lidocaine effect on neutrophilic inflammation. However, in rabbit studies of endotoxin‐induced acute lung injury, delivery of IV lidocaine at 0.03 mg/kg/min (plasma lidocaine concentrations not provided) significantly decreases neutrophilic infiltration into pulmonary parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine also decreases expression of adhesion molecules, which impairs neutrophil extravasation. [1][2][3] Prophylactic lidocaine therapy has shown promise in animal models of acute lung injury where it decreases pulmonary neutrophilic inflammation. 4 Asthmatic patients treated with nebulized lidocaine show improved clinical signs and lung function and decreased reliance on bronchodilator therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…82 PMN and macrophage functions (including chemotaxis, adherence, production of toxic oxygen species, phagocytosis, and cytokine release) are inhibited by LAs. 10,12,13,70,84,191 Lidocaine has been shown to inhibit cell proliferation, cytokine production, and mitogen-activated protein kinase activation in T cells and upregulate regulatory T-cells that promote an antiinflammatory t-cell phenotype. 84,94,101,118 One study in mouse showed that release of antiinflammatory cytokine IL10 may be enhanced by lidocaine.…”
Section: Local Anestheticsmentioning
confidence: 99%